Importance of Instructor Presence and Human Connection in Education. - Wilborn, Marcus; Chelladurai, Rayola; Livingston, Manuel; Stelmark, Jarek (Radiologic Technology)
The article focuses on the critical role of instructor presence and human connection in radiologic technology education, especially as programs increasingly adopt virtual simulations, hybrid, and online learning models. Instructor presence—defined as educators being visible, responsive, and emotionally available—supports not only technical skill acquisition but also ethical reasoning, emotional resilience, and professional identity development. Research indicates that sustained instructor engagement enhances student motivation, satisfaction, clinical confidence, and preparedness, while its absence can lead to feelings of isolation and hinder deeper learning. The article emphasizes that maintaining instructor presence across digital platforms requires deliberate strategies and institutional support, as it remains essential for fostering meaningful student-instructor relationships and ensuring quality clinical education outcomes.